PENGARUH PERILAKU WAJIB PAJAK MENGENAI PEMAHAMAN DAN KESADARAN TERHADAP KEPATUHAN MEMENUHI WAJIB PAJAK - Dahruji Inar (BALANCE: Economic, Business, Management and Accounting Journal, 2010)
This research is associative, the study titled "Effect of Taxpayer Behavior Regarding the level of understanding and awareness Taxpayers Taxpayers Against The Taxpayer Compliance Liabilities In Addressing taxation", empirical studies on individual taxpayers in the District of Bangkalan. This research aims to to determine the effect between two or more variables. This study proves the hypothesis that the taxpayer awareness and understanding of the taxpayer to have effect on an individual taxpayer compliance. Based on research conducted in conjunction with data analysis and testing, it was found that the taxpayer awareness of the partial effect on the compliance of the taxpayer. So is the understanding by the partial taxpayer also affect taxpayer compliance. In addition, jointly or taxpayer awareness and understanding of tax payers also have an impact on taxpayer compliance. Key words: awareness of the taxpayer, the taxpayer understanding, compliance of the tax payer.